Recalling and Updating Research on Diamagnetic Cavities: Experiments, Theory, Simulations - Winske, Dan; Huba, Joseph D.; Niemann, Christoph; Le, Ari (Frontiers in Astronomy and Space Sciences, 2019)
In the decade from the mid 80’s to the mid 90’s there was considerable interest in the generation of diamagnetic cavities produced by the sub-Alfvenic expansion of heavy ions across a background magnetic field. Examples included the AMPTE and CRRES barium releases in the magnetotail and magnetosphere as well as laser experiments at various laboratories in the United States and the Soviet Union. In all of these experiments field-aligned striations and other small-scale structures were produced as the cavities formed. Local and non-local linear theory as well as full particle (PIC), hybrid and Hall-MHD simulations (mostly 2-D) were developed and used to understand at least qualitatively the features of these experiments. Much of this review is a summary of this work, with the addition of some new 3-D PIC and Hall-MHD simulations that clarify old issues associated with the origin and evolution of cavities and their surface features. In the last part of this review we discuss recent extensions of the earlier efforts: new space observations of cavity-like structures as well as new laboratory experiments and calculations with greatly improved diagnostics of cavities formed by expansions of laser-produced ions at super-Alfvenic speeds both across and along the background magnetic field.